2022
DOI: 10.12669/pjms.38.4.5203
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effect of reduning combined with gamma globulin treatment on symptom improvement serum levels of IL-6, 25-(OH)D and LDH in children with severe mycoplasma pneumonia

Abstract: Objectives: To investigate the effects of Reduning combined with gamma globulin on symptom improvement and serum levels of interleukin-6 (IL-6), 25-hydroxyvitamin D[25-(OH)D] and lactate dehydrogenase (LDH) in children with severe mycoplasma pneumonia (MP). Methods: A total of 123 children with severe MP admitted to the Changzhou Cancer Hospital affiliated to Soochow University from May 2018 to April 2020 were selected as subjects and randomly divided into three groups: control Group-A, control Group-B a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…25 (OH) D is a neuroendocrine immune regulatory hormone that can regulate the balance of calcium and phosphorus, act on neutrophils, macrophages, and lymphocytes, and stimulate the expression of antimicrobial peptides, thereby affecting the body's inflammatory response and antimicrobial activity. 16 Research suggested that long-term 25 (OH) D deficiency could promote the occurrence of oxidative stress, leading to the occurrence of chronic inflammation. Adequate levels of 25 (OH) D inhibited the release of inflammatory cytokines such as interleukin-6 and tumor necrosis factor-α.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 (OH) D is a neuroendocrine immune regulatory hormone that can regulate the balance of calcium and phosphorus, act on neutrophils, macrophages, and lymphocytes, and stimulate the expression of antimicrobial peptides, thereby affecting the body's inflammatory response and antimicrobial activity. 16 Research suggested that long-term 25 (OH) D deficiency could promote the occurrence of oxidative stress, leading to the occurrence of chronic inflammation. Adequate levels of 25 (OH) D inhibited the release of inflammatory cytokines such as interleukin-6 and tumor necrosis factor-α.…”
Section: Discussionmentioning
confidence: 99%
“…25 (OH) D is a neuroendocrine immune regulatory hormone that can regulate the balance of calcium and phosphorus, act on neutrophils, macrophages, and lymphocytes, and stimulate the expression of antimicrobial peptides, thereby affecting the body's inflammatory response and antimicrobial activity. 16…”
Section: Discussionmentioning
confidence: 99%
“…Despite major advances in its prevention and treatment, pneumonia remains the primary cause of death in children outside the neonatal period. 11 There are many risk factors leading to pediatric pneumonia, including age, malnutrition, immunosuppression, pathogenic microbial infection, etc., 12 , 13 among which pulmonary inflammation caused by pathogens such as viruses and bacteria is the most common. 14 Pediatric pneumonia is mainly manifested clinically as fever, cough, shortness of breath and dyspnea, wet rales on lung auscultation, and inflammatory lesions found on chest imaging examination.…”
Section: Discussionmentioning
confidence: 99%
“…The primary therapeutic approaches for pediatric pneumonia can be separated into etiological treatment and symptomatic treatment. The preferred approach for etiological treatment is antiviral vitamin therapy [24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%